Postpartum Psychiatric Admissions in the United States - Wen, Timothy; Fein, Arielle W.; Wright, Jason D.; Mack, William J.; Attenello, Frank J.; D'Alton, Mary E.; Friedman, Alexander M. (American Journal of Perinatology, 2019)
Objective This study aimed to assess risk for postpartum psychiatric admissions in the United States.Study Design This study used the 2010 to 2014 Nationwide Readmissions Database to identify psychiatric admissions during the first 60 days after delivery hospitalization. Timing of admission after delivery discharge was determined. We fit multivariable log-linear regression models to assess the impact of psychiatric comorbidity on admission risk, adjusting for patient, obstetrical, and hospital factors.Results Of 15.7 million deliveries from 2010 to 2014, 11,497 women (0.07%) were readmitted for a primary psychiatric diagnosis within 60 days postpartum. Psychiatric admissions occurred relatively consistently across 10-day periods after delivery hospitalization discharge. Psychiatric diagnoses were present among 5% of women at delivery but 40% of women who were readmitted postpartum for a psychiatric indication. In the adjusted model, women with psychiatric diagnoses at delivery hospitalization were 9.7 times more likely to be readmitted compared with those without psychiatric comorbidity. Women at highest risk for psychiatric admission were those with Medicare and Medicaid, in lower income quartiles, and of younger age.Conclusion While a large proportion of psychiatric admissions occurred among a relatively small proportion of at-risk women, admissions occurred over a broad temporal period relative to other indications for postpartum admission.
Keywords: postpartum depression; psychiatric readmissions; obstetric conditions; maternal risk